Development of classroom design model into character education in elementary - Abna Hidayati; Mutiara Felicita Amsal; Winanda Amilia (International Conferences on Educational, Social Sciences and Technology)
Implementation of character education in elementary school level of its effectiveness is strongly supported by the design of learning environment and classroom with characteristic character. Initial phenomena indicate that many classrooms in elementary schools are not supported by the design of the nuanced space character education, so the implementation of character education is less effective. This study aims to determine the model of nuanced classroom character education in primary schools. The method of research is development research using the procedural development model of Borg and Gall. The trial was conducted at the target school, SD 08 Nanggalo Padang which is a pilot project for the implementation of character education in elementary school. The results showed that the design of learning environment of character education consists of group position, classroom equipped with wet and dry garbage bin, findings of lost items, suggestion box, list of lessons and picket list.